Social support programs: its effects on girls schooling and reducing dropping out of school in the northeast middle Atlas – Morocco - El-Alami, Abdelilah; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Arab Journal for Sciences and Research Publishing, 2024)
Morocco has made concrete efforts to reform the education and training system by placing it in second place on the list of priorities, this article comes in this context through which we will stand on its social support programs and its effects on girls’ schooling reducing dropping out of school and encouraging schooling in the northeastern Middle Atlas as a financial management with an educational aim, by answering the following problem: How do forms of social support based on governance and the optimal use of capabilities contribute to achieving the quality of schooling and reducing the number of drop out students in the territorial communities studied?, The study revealed that while public schools enroll many girls, a significant portion remains out of school, particularly in primary education (76.33% enrollment compared to 81.21% in traditional primary schools). Uneven student distribution across municipalities with a focus on primary schools, balanced participation in the school support program (around 50% in primary and 45% in secondary), limited schools in villages (67.47% lacking), and inadequate facilities all hinder girls’ education.